Structural Dynamic of FLS2 LRR D122N BAK1 LRR Crystal Complex - Rodoshi, Anika Tasfia (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.